KEANEKARAGAMAN KERANG (MOLLUSCA: BIVALVIA) DI KAWASAN SERANGAN, DENPASAR, BALI - Suratul Wahyuda; Ni Made Suartini; Deny Suhernawan Yusup (SIMBIOSIS, 2024)
Throughout the waters of the island of Bali, clam are a very valuable biological resource. The Serangan area in Denpasar, Bali, is one of the areas that has lots of clam which are widely used as food. The objective of this research is to identify clam species found in the Serangan Area, those that are collected for consumption by the community, and to determine the values of diversity index, evenness, and dominance of clams in the Serangan Area. The research stations are divided into three with a distance between stations of 250 m. At each station a transect is made perpendicular to the shoreline with a distance between transects of 10 m. Each transect at the station was made 10 sampling quadrants measuring 50x50 cm. The research results revealed that there were eight species of clams found. Four of these species were commonly collected for consumption by the community, namely Marcia hiantina, Anadara antiquata, Meretrix meretrix, and Pinna muricata. The Marcia hiantina species was the most frequently collected for consumption. The diversity index values fell within the moderate category, ranging from 1.10 to 1.39. The evenness index values were categorized as high, ranging from 0.92 to 1.00, and were supported by low dominance index values ranging from 0.25 to 0.33.